Metabolic derangements in the gastrocnemius and the effect of Compound A therapy in a murine model of cancer cachexia. Issue 2 (24th January 2013) - Der-Torossian, Hirak; Wysong, Ashley; Shadfar, Scott; Willis, Monte S.; McDunn, Jonathan; Couch, Marion E.
Abstract : Background: Cancer cachexia is a severe wasting syndrome characterized by the progressive loss of lean body mass and systemic inflammation. Inhibiting the signaling of the transcription factor nuclear factor kappa B (NF‐κB) largely prevents cancer‐induced muscle wasting in murine models. We have previously shown the utility of Compound A, a highly selective novel NF‐κB inhibitor that targets the IκB kinase complex, to provide clinical benefit in cancer‐induced skeletal muscle and cardiac atrophy. Methods: Using a metabolomics approach, we describe the changes found between cachectic and noncachectic gastrocnemius muscles before and after Compound A treatment at various doses. Results: Of the 234 metabolites in the gastrocnemius, cachexia‐induced changes in gastrocnemius metabolism reset the steady‐state abundances of 42 metabolites ( p  < 0.05). These changes, not evenly distributed across biochemical categories, are concentrated in amino acids, peptides, carbohydrates and energetics intermediates, and lipids. The gastrocnemius glycolytic pathway is markedly altered—changes consistent with tumor Warburg physiology. This is the first account of a Warburg effect that is not exclusively restricted to cancer cells or rapidly proliferating nonmalignant cells. Cachectic gastrocnemius also displays tricarboxylic acid cycle disruptions, signs of oxidative stress, and impaired redox homeostasis. Compound A only partially rescues the phenotype of the cachectic gastrocnemius, failing to restore the gastrocnemius' baseline metabolic profile. Conclusions: The findings in the present manuscript enumerate the metabolic consequences of cachexia in the gastrocnemius and demonstrate that NF‐kB targeted treatment only partly rescues the cachectic metabolic phenotype. These data strengthen the previous findings from metabolomic characterization of serum in cachectic animals, suggesting that many of the metabolic alterations observed in the blood originate in the diseased muscle. These findings provide significant insight into the complex pathophysiology of cancer cachexia and provide objective criteria for evaluating future therapeutics. Electronic supplementary material: The online version of this article (doi:10.1007/s13539‐012‐0101‐7) contains supplementary material, which is available to authorized users.